Gegar Budaya Mahasiswa Indonesia dalam Komunikasi Antarbudaya di Luar Negeri - Hadiniyati, Ghina; Annisa, Dennisa Teguh; Nugroho, Catur; Lestari, Dannisa Maulita (Jurnal Pekommas, 2023)
In this globalization era, everyone in the world has equal opportunities to collaborate and compete globally. As experienced by Indonesian students in overseas countries who are studying abroad. The purpose of this research is to discuss cross-cultural communication including language adaptation, culture shock, and the process of cultural acceptance experienced by these students. This research uses a qualitative method with a phenomenological approach with a semi structured interview with Indonesian students in overseas countries such as Malaysia, Egypt, China, England, Germany, South Korea, and Canada as data collective techniques. The result of this research shows that in the cross-cultural communication process experienced by the students, various kinds of culture shock and obstacles related to language occurred. So, the adaptation process carried out by the informants in this research focused on these two things. In the future research, discussion about culture shock can be developed specifically and deeper, including the causative factors, process, effects, and the solution.